The Effect of Welding Speed on the Physical and Mechanical Properties of Low Carbon Steel Welded Joints Using TIG Welding Using 2 External Magnetic Fields - Fajar Paundra; Andi Prabowo; M Farhan Sidik; Abdul Muhyi; Eko Pujiyulianto; Farid Nanda Syanur; Ariyo Nurachman Satiya Permata (Journal of Industrial and Mechanical Engineering, 2024)
The use of external magnetic fields is very influential in TIG (Tungsten Inert Gas) welding because it can disrupt the stability of the electric arc formed between the tungsten electrode and the base metal. Magnetic fields can cause the arc to distort or shift, resulting in uneven and low quality welds. TIG (Tungsten Inert Gas) is a welding method that uses a non-melting tungsten electrode to produce a weld. This study aims to determine the effect of external magnetic field on the quality of TIG welding results. This research uses the TIG (Tungsten Inert Gas) welding process on low carbon steel material with speed variations of 4 mm/s, 6 mm/s, 8 mm/s and 10 mm/s and uses 2 Neodymium type external magnetic fields. Tests carried out on the results of welding joints are Vickers hardness test, micro & macro structure test. The highest hardness test value was obtained in the 4 mm/s welding speed variation using 2 external magnetic fields with a hardness value of 187.388 HVN. Microstructure testing shows that the base metal contains ferrite and pearlite structures. In the HAZ (Heat Affected Zone) area there are ferrite, pearlite and martensite structures. Macro structure testing shows several welding defects, including porosity, imperfect penetration, underfill and irregular surface. The use of two external magnetic fields can affect the results of TIG welding itself, such as deepening the penetration of welding so as to produce a good welding joint. Some things you should pay attention to if you don't want welding defects to occur are paying attention to the distance between the electric arc and the material, and the torch must be parallel to the welding line.